1992
DOI: 10.1002/app.1992.070451016
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of wool‐g‐poly(methyl methacrylate) copolymers

Abstract: SYNOPSISThe thermal properties of wool fibers can be improved by graft copolymerization with vinyl monomers. Using TGA, DTG, and DSC techniques, the thermal behavior of methyl methacrylate grafted wool fibers was studied. Graft copolymerization was carried out using KBr03 and substrates such as Fe( 11), Co( 11), cysteine, cystine, tyrosine, and urea. Of all the systems studied the grafted fibers which involve Fe( II), Co (II), and cystine gave improvement in the thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…with different thermal stability, belonging to sepThe storage component of the dynamic modulus arated fiber domains. [23][24][25][26][27][28][29] With increasing add on of untreated wool [ Fig. 4(a)] decreased slightly of poly(BzMA)-grafted wool fibers, the intensity in the low temperature range, from 050 to 20ЊC, of the endotherm in the high-temperature side and then remained stable until about 165-170ЊC.…”
Section: Resultsmentioning
confidence: 99%
“…with different thermal stability, belonging to sepThe storage component of the dynamic modulus arated fiber domains. [23][24][25][26][27][28][29] With increasing add on of untreated wool [ Fig. 4(a)] decreased slightly of poly(BzMA)-grafted wool fibers, the intensity in the low temperature range, from 050 to 20ЊC, of the endotherm in the high-temperature side and then remained stable until about 165-170ЊC.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning polyacrylates, Elangovan and Saccubai observed that the graft copolymerization of methyl methacrylate (MMA) onto the wool surface improves the acid/alkali resistances and the dye uptake, also increasing the wool's tensile strength [139] and thermal properties [140]. Xu et al [141] studied the graft polymerization of hydroxyethyl methacrylate (HEMA) onto woollen fabrics by microwave irradiation, yielding a much higher graft add-on by improving the monomer's reactivity in comparison to conventional heating.…”
Section: Polyacrylates Polyacrylonitrile (Pan) and Polyacrylamide (Pam)mentioning
confidence: 99%